OPTIMIZATION OF SHELL AND TUBE HEAT EXCHANGER DESIGN WITH INCLINED BAFFLES - Rahman, Aulia; Winarto, Winarto; Siswanto, Eko (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
Shell and tube heat exchanger (STHeX) design development continues to be carried out to increase the effectiveness of a system. One way is to investigate the optimal baffle design. The new structure of STHeX with Inclined-Segmental Baffles is further investigated. The experiment was carried out using the numerical method Computing Fluid Dynamics (CFD) software with three-dimensional modeling. The results show that the heat change coefficient value is lower than conventional STHeX, However, the pressure drop value is reduced quite significantly. Therefore, it is necessary to know the overall heat transfer coefficient value per pressure loss (U/DeltaP). Hence, we get U/DeltaP values of 0.9 and 0.68 for STHeX with Inclined-Segmental Baffle and conventional STHeX, respectively. Thus, there is a significant increase ranging from 37-34%. It is concluded that STHeX with Inclined-Segmental baffles increases the U/DeltaP value significantly compared to conventional STHeX.